[Mauerrest eines alten Besichtigungsturmes am Breiten Tore] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia rozbiórkę baszty przy Szerokiej Bramie, 02.06. 1912 r.